HISTORICAL ANALYSIS AND MANAGEMENT ON FLOODS DURING PANDEMIC COVID-19 IN DKI JAKARTA INDONESIA - Fenti Nur Azizah; Moses Glorino Rumambo Pandin (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
A flood is an event that occurs due to an accumulation of water that falls and cannot be accommodated by the ground. Thestudy aims to find out the history of floods in DKI Jakarta and the handling of floods amid the current Covid-19 pandemic. Natural events, such as floods, are not new in an urban area. The study discusses whyfloods that occur in urban areas, especially the DKI Jakarta area, are an annual cycle?.But there is a difference in 2020 and 2021 because of the flood, this time amid the Covid-19 pandemic, so extra handling is needed because if there is a crowd in the refugee camp it can spread the virus more widely. Thus, the government is doing everything it can to handle floods so that the community remains in a healthy body condition. The method used in the study is descriptive with a literature study approach, namely collecting data from reliable sources.Floods can be caused by two factors, namely natural causes and unnatural causes (from human activities).